(untitled) (The Review of Diabetic Studies, 2025)
This research aims to study the role of smartphone applications in improving ambulance response speed, focusing on the "Asafni" application as an applied model. The importance of this study stems from the growing role of smart technologies in supporting emergency medical services, and the efforts of health authorities to reduce the time required to reach critical cases and improve the field performance of ambulance teams. The study relied on the descriptive analytical approach, and a questionnaire consisting of (15) items was applied to a sample of (200) employees working in the “As’afni” application and cadres affiliated with the ambulance sector in different regions of the Kingdom of Saudi Arabia. The survey addressed several topics, including: speed of receiving reports, accuracy of geolocation, improved communication between the reporter and field teams, reduced communication errors, and increased beneficiary satisfaction with emergency services. The study results showed that the "Asafni" app significantly contributes to accelerating ambulance response times and improving the quality of emergency services. The majority of sample members indicated the app’s effectiveness in accurately identifying locations and facilitating the immediate exchange of information between the reporter and ambulance teams, in addition to its role in enhancing coordination and field decision-making. The study also recommended the need to expand the application on a broader national scale and enhance training and qualification programs for staff to ensure optimal use of digital technologies in ambulance services.